Índices morfo-fisiológicos e produtividade de cultivares de jambu influenciadas pela adubação orgânica e mineral - Borges, Luciana da Silva; Goto, Rumy [UNESP]; Lima, Giuseppina Pace Pereira [UNESP] (My University, 2014)
The jambu belongs to the family Asteraceae, tropical crop, nowadays, this plant has been considered as a promising vegetable crop, because to its pharmacological properties. Despite this novelty, the vegetable remains invisible in the statistics of production and market in the state of Pará, Brazil. This research was carried out with the aim of comparing the economic productivity and phenological development by the morpho-physiological growth indexes of two cultivars of jambu organic manure and mineral fertilizers. The experiment was carried out at the São Manuel Experimental Farm (São Manuel-SP), which belongs to the Faculdade de Ciências Agronômicas - UNESP, campus Botucatu. The experimental design was a factorial randomized blocks (2 x 2) with two fertilization (organic and mineral) and two cultivars (Jambuarana and Nazareth), with six replications, two fertilization (organic and mineral) and two cultivars (Jambuarana and Nazareth). The following characteristics were evaluated: Plant height (cm), Leaf area (cm2), Fresh mass (g), Dry mass (g), Leaf area index (LAI), Leaf area ratio (LAR) , Specific leaf Area (SLA), Leaf Weight Ratio (LWR), Amount of water in the plant (QAPA) (g per plant set), Leaf specific weight (LSW) (g cm-2per plant set) and Economic productivity. All data were statistically analyzed by analysis of variance and the Tukey test (1%) for mean comparison, with the software SISVAR. In the conditions of this experiment was carried out, it was possible to verify that the cultivar Jamburana had not only a good agronomic development and economic productivity under organic fertilization but also the best morpho-physiological indexes, showing that this kind of fertilization increases the agronomic effectiveness of this cultivar.
Morpho-physiological indices and economic productivity of jambu cultivars influenced by the organic and mineral fertilizers
Keywords: Biomass; Phenology; Productivity; Spilanthes oleracea